Redefining Sustainability: A Review of the Big Names from the FMCG Industry Taking Significant Measures - Sharma , Chinmay; Sharma , Raghvendra Kumar (International Journal of Membrane Science and Technology, 2023)
Human resource is one of the most crucial factors in the organization. Recent years have shown an inclination towards sustainability among organizations. Sustainability calls for a particular set of guidelines to ensure that we are making optimum utilization of resources without causing any harm to the environment. For the past few years, many researchers have been actively working on this issue and summarized their findings in research papers. Past studies reveal that many organizations consider sustainability a critical issue and continually work on improving their strategies. This study aims to discover the factors that gave rise to the concept of Green Human Resource Management, how it evolved with the dynamic market and what contributions have been made by top brands through their Green HRM policies. Purpose: The purpose of the study was to highlight the working patterns of high performing companies from the FMCG industry. The ideology behind the study was to track the steps taken by big brands towards betterment of the society and towards the environment. Theoretical framework: This study aims at highlighting the concerns of today that might severely affect market and the society in the future. Since HRM practices contribute to the implementation and upkeep of an environmental management system (EMS), helping organizations achieve higher environmental performance (EP), it is becoming increasingly clear that the environmental impacts of HRM processes should be taken into account at every stage of the process (Gilal et al., 2019; Yusoff et al., 2020). In reality, GHRM makes sure businesses extend widely and adopt more ecologically responsible practices. GHRM is crucial for business management for a number of reasons, including the advantages to the environment, retaining employees, and boosting a company’s appeal. According to earlier HRM literature (Pham et al., 2020; Awan et al., 2022) individual practices, rather than a collection of practices, had a greater impact on a company’s success. Design/ Methodology/ Approach: The study is primarily based on past researches and data directly referred from the companies’ sources for utmost authentication of facts added. Findings: Big brands are taking initiatives like reducing the carbon footprint by taking certain actions basis the chain they ae dealing in. The companies are not only making strategies for the same, but also taking a step in creating awareness regarding the hot topic. Research, Practical & Social implications: Sustainability is becoming a need for the hour considering the limit of the resources that we possess today. Major factor while extracting resources is the make sure that we are putting in extra effort to replenish those resources. For instance, paper. If we want two trees for paper, we must plant at least four trees to make up for the damage we are doing today. Thus, if we want to make sure that our future generations would be able to access and use resources as we are doing today, we must follow certain self-made rules for the same.